PERTIMBANGAN KEBERLANJUTAN DALAM PERUBAHAN PERUNTUKAN LAHAN PERTANIAN DI KABUPATEN BEKASI - Yunita Ismail Masjud (Journal of Environmental Engineering and Waste Management, 2018)
Changes in land use require consideration of the sustainability of the area. The principle of a triple bottom line in sustainable development must be applied. This research builds a sustainable development model in Bekasi Regency. The secondary data used is from the Central Bureau of Statistics of Bekasi Regency. The variables used are the average of rainfall, the number of population, the number of job seekers, the area of rice field, the area of rice harvest, the production of wetland rice, and the production of field rice as independent variable and GDP as the dependent variable. Consideration of the selection of variables by looking at the economic, social and environmental aspects that are aspects that determine the sustainability of development. Data analysis was done by using multiple linear regression. The results showed that the population, paddy field area, paddy field production have a significant positive effect to PDRB, while the number of job seekers, paddy field area, and paddy field production significantly negatively. The average variable of rainfall has no significant effect to GRDP. Taken together (simultaneously) all the independent variables have a significant effect on GRDP.